2024
DOI: 10.3390/buildings14030807
|View full text |Cite
|
Sign up to set email alerts
|

Flawed Institutional Structures: Project Managers Underutilized in Nigeria’s Construction Industry

Ebuka Valentine Iroha,
Tsunemi Watanabe,
Tsuchiya Satoshi

Abstract: Many studies have been conducted on the poor performance of the construction industry. Nigeria’s construction industry has been linked to project delays and cost overruns, leading to many abandoned construction projects throughout the country. These issues are largely attributed to inadequate project management practices and the underutilization of project managers. To address these challenges, an institutional analysis was conducted to examine the factors, within the institutional framework of the Nigerian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…The study found that employees experiencing job insecurity tend to exhibit higher levels of absenteeism, presenteeism, and reduced commitment to safety practices. Moreover, a study by Iroha et al [74] argued that job insecurity undermines trust between employees and management, leading to a breakdown in communication and cooperation regarding safety issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that employees experiencing job insecurity tend to exhibit higher levels of absenteeism, presenteeism, and reduced commitment to safety practices. Moreover, a study by Iroha et al [74] argued that job insecurity undermines trust between employees and management, leading to a breakdown in communication and cooperation regarding safety issues.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that job insecurity undermines adherence to safety guidelines as workers focus on job retention rather than safety compliance [72][73][74]. Ensuring job security can therefore improve adherence to safety protocols.…”
Section: H9 Regulatory Environments (Res) Positively Influence Asgsmentioning
confidence: 99%